CORRELATIONS OF SHIFT WORK 2-2-2(2) ROTATION ON SLEEP QUALITY AND FATIGUE OF NURSES IBNU SINA GRESIK GENERAL HOSPITAL - Saikhunuddin; Widajati, Noeroel (Faculty of Vocational Studies, Universitas Airlangga, 2024)
Background: Working as a nurse in a hospital required to work with a shift system. Working with the shift system (morning, afternoon, and night) can affect the circadian rhythm, which has the potential to cause sleep disturbances and fatigue. Purpose: This research aims to analyze the influence of shift work rotation 2-2-2(2) on sleep quality and fatigue in nurses with shift work systems in inpatient rooms at General Hospital Ibnu Sina Gresik. Method: This research was an observational analytics study with a cross-sectional design. The total sample was 80 nurses in an inpatient care unit with a shift work system chosen through purposive sampling techniques. The Subjective Self-Rating Test (SSRT) issued by the Industrial Fatigue Research Committee (IFRC) questionnaire was used for the measurement of fatigue, and the Pittsburgh Sleep Quality Index questionnaire (PSQI) was used for the assessment of sleep quality. Univariate and bivariate analyses were done with a Chi-square statistical test. Result: The study showed that most respondents had good sleep quality (87.5%), and most had low tiredness (71.2%). The Chi-square test results obtained a p-value of 0.224 > 0.05 and a p-value of 0.108 > 0.05, meaning there were no correlations between shift work and sleep quality and fatigue. Conclusion: Shift work had no relationship with sleep quality and fatigue. Appropriate shift work arrangements can contribute to reducing the negative impact of shift work.